Back Cover: Predestined Steady‐State Entanglement under Pure Vacuum Noise (Adv. Quantum Technol. 3/2023). Issue 3 (10th March 2023) - Zhou, Yuebing; Hu, Jiawei; Yu, Hongwei
Abstract : For a pair of rotating qubits under pure vacuum noise with appropriate orbital radius and angular velocity, entanglement is not only resilient against vacuum noise for initially entangled states, but is also predestined to be created and be preserved for arbitrary initially separable states. More details can be found in article number 2200159 by Yuebing Zhou, Jiawei Hu, and Hongwei Yu.